Pengaruh Penggunaan Polimer Terhadap Kualitas Batubara di PT. Bhumi Sriwijaya Perdana Coal, Desa Bero Jaya Timur, Kecamatan Tungkal Jaya, Kabupaten Musi Banyuasin, Sumatera Selatan - RIDHO FADHIL HERNAWAN; Heri Prabowo (Departemen Teknik Pertambangan FT UNP, 2022)
PT. Bhumi Sriwijaya Perdana Coal (PT. BSPC) is a coal mining company located in East Bero Jaya Village, Tungkal Jaya District, Musi Banyuasin Regency, West Sumatra Province. PT. BSPC implements an open pit mining system. The quality of coal in PT. Bhumi Sriwijaya Perdana Coal has a very high total moisture, which contains 45%. With the high total moisture content contained in coal, PT. BSPC innovates by using chemicals containing polymers to maintain total moisture, ash content and calorific value. The research method used is quantitative which refers to experimental research. In the research conducted, there was a change in the value of coal parameters. The tests carried out were 1 ton and 10 tons of coal given 50 liters of water and 1 liter of chemicals by comparing the effectiveness of using Supercoat (P1) and Coalguard (P2). The result obtained was a decrease in the value of TM on coal of 1 ton and 10 tons. In 1 ton of coal, there was a decrease in TM values for P1 and P2 by 0.15% and 0.47%. decrease in Ash values for P1 and P2 by 1.61% and 2.22%. and for caloric values for P1 and P2 there was an increase of 122 kcal/kg and 131 kcal/kg. in 10 tons of coal there was a decrease in the TM value for P1 and P2 by 4.74% and 5.51%. decreased Ash values for P1 and P2 by 2.83% and 3.24% and for caloric values for P1 and P2 there was an increase of 317 kcal/kg and 394 kcal/kg. Based on the results of tests that have been carried out, it can be concluded that the use of a more effective chemical is Coalguard at a 10-ton test.